2003
DOI: 10.1590/s0001-37652003000300004
|View full text |Cite
|
Sign up to set email alerts
|

Somatic pairing, endomitosis and chromosome aberrations in snakes (Viperidae and Colubridae)

Abstract: The positioning of macrochromosomes of Bothrops jararaca and Bothrops insularis (Viperidae) was studied in undistorted radial metaphases of uncultured cells (spermatogonia and oogonia) not subjected to spindle inhibitors. Colchicinized metaphases from uncultured (spleen and intestine) and cultured tissues (blood) were also analyzed. We report two antagonic non-random chromosome arrangements in untreated premeiotic cells: the parallel configuration with homologue chromosomes associated side by side in the metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
2
13
0
3
Order By: Relevance
“…Interstitial C-bands were seldom reported (Oguiura et al 2010). While, Beçak et al (2003) reported that among Colubridae species there is wild variation of chromosome number and different levels of sex chromosome differentiation. A common feature in Reptilia is the presence of macrochromosomes and microchromosomes, probably due to karyological ancestral derivation from forms that already presented this attribute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interstitial C-bands were seldom reported (Oguiura et al 2010). While, Beçak et al (2003) reported that among Colubridae species there is wild variation of chromosome number and different levels of sex chromosome differentiation. A common feature in Reptilia is the presence of macrochromosomes and microchromosomes, probably due to karyological ancestral derivation from forms that already presented this attribute.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, even microchromosomes that are apparently totally heterochromatic may have some euchromatin in them. This condition may be or not advantageous, depending on environmental conditions (Olmo 2005, 2008, Beçak et al 2003. Hydrodynastes bicinctus bicinctus has 2n=24, a very small diploid chromosome number for snakes and no microchromosomes (Beçak and Beçak 1969), which may be interpreted as a formation of favorable linkage groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They could be due to a reawakening process of normal G 0 /G 1 diploid, flat cells and/or to a special type of mitotic division of endopolyploid cells. [13][14][15][16] Polyploidy associated with senescence is generally assessed by flow cytometry which gives no information as to mode of mitotic cycling. 2,[17][18][19] The special type of endopolyploidy had shown production of genome reduced cells (e.g., 4n/8C to 2n/2C) with chromosomal abnormalities occurring immediately before (i.e., pre-senescence) the change to flat cells-only.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier literature associated the tetraploid-condition with formation of 46, 4-chromatid diplochromosomes (4n/8C) i.e., from endo-reduplication [10] [28]. Presently there is increasing mentioning of endoreplication, but its chromosomal structural consequence (4-chromatid chromosomes) as distinct from regular, genomic doubling to 92 chromosomes lacks understanding regarding a non-mitotic division [29]- [32]. Even when encountered in cancer-cytogenetics, there appears to be no curiosity about their division-behavior, which was a major interest for mouse ascites tumor cells some decades ago [33].…”
Section: ) Reductive Endopolyploidy Creating a Cancerous Potentialmentioning
confidence: 99%